2019
DOI: 10.1007/s10876-019-01694-6
|View full text |Cite
|
Sign up to set email alerts
|

Green Nanocolloids Control Multi Drug Resistant Pathogenic Bacteria

Abstract: Cymbopogon citratus is grown globally for therapeutic application is utilized to synthesize colloidal silver nanoparticles (CcAgNps). CcAgNps are characterized by biophysical methods and are tested against CTXM-15 expressing pathogenic Escherichia coli strains. MIC, MBC and biofilm assays are performed at different concentrations of nanoparticles. The expression of CTXM-15 gene responsible for antibiotic resistance is analyzed by polymerase chain reaction to identify the role of CTXM-15 in pathogenesis. CcAgNp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The shape, size, and surface charge of CANCs play critical role in penetrating into the biofilm layer and kill the organism by anyone of the mechanism such as ROS production, cell wall damage, DNA damage etc. In previous studies it was reported that polyphenolic compounds, tannins, terpenoids, flavonoids, which are present in the plant extracts, acted as a siderophores, which chelates the metal from the growth medium and degrades the biofilm (Sharma et al 2016 ).Similar results were supporting in our study, in such a way that citronella extracts were rich in polyphenols, tannins, terpenoids, flavonoids which acted as a reducing agent during nanocolloid synthesis, which reacted as quorum quenchers by disturbing the biofilm formation by preventing the cell to cell communication (Qing et al 2018 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The shape, size, and surface charge of CANCs play critical role in penetrating into the biofilm layer and kill the organism by anyone of the mechanism such as ROS production, cell wall damage, DNA damage etc. In previous studies it was reported that polyphenolic compounds, tannins, terpenoids, flavonoids, which are present in the plant extracts, acted as a siderophores, which chelates the metal from the growth medium and degrades the biofilm (Sharma et al 2016 ).Similar results were supporting in our study, in such a way that citronella extracts were rich in polyphenols, tannins, terpenoids, flavonoids which acted as a reducing agent during nanocolloid synthesis, which reacted as quorum quenchers by disturbing the biofilm formation by preventing the cell to cell communication (Qing et al 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…From the result of CTX-M-15 gene expression studies, it can be hypothesized that CANCs suppress CTX-M-15 gene expression which in turn reduce the transcription and translation of enzyme which is responsible for antibiotic degradation. There were previous report supporting that silver ions directly interact with DNA, RNA and protein, which disturb the central dogma of the cell (Qing et al 2018 ). Thus, reproductive mechanism of the organism will be prevented, which ultimately reduces the pathogenicity of microorganism through various means such biofilm inhibitor, suppressing the antibiotic resistant genes etc., (Peirano et.al.…”
Section: Discussionmentioning
confidence: 95%
“…This helps us to identify the possible biomolecules, which could play the role in reduction, stabilization and capping during synthesis of myconanoparticles. (Perkin Elmer Spectrum100 FT-IR) (20)(21)(22)(23). Colloidal nanoparticle solution was used to identify the hydrodynamic size (Z average), polydispersity index (PDI), and surface charge (zeta potential) of the synthesized nanoparticles using particle size analyser combined with zeta analyser (Malvern Instruments Ltd, UK).…”
Section: Physio-chemical Characterization Of Green Silver Nanoparticlesmentioning
confidence: 99%
“…It was followed by ltering through grade1 lter paper thrice to clarify the syrup. Then, the concentrated syrup was stored at 4 0 C for further use (Ranjani et al 2019a). Qualitative phytochemical screening of citronella grass extract was carried out using standard methods (Harborne 1973).…”
Section: Preparation Of Citronella Extractmentioning
confidence: 99%